Inhibitory effect of vanillin on Pseudomonas syringae pv. actinidiae of kiwifruit surface and its effect on the quality of fruits - Lin, Wenli; Li, Wen; Huang, Tianyu; Yin, Chunfeng; Liu, Fang; Gong, Biya; He, Kejia; Xiao, Fulian; Yang, Shuizhi; Bu, Fanwen; Tang, Fang; Cao, Jinhua (Frontiers in Sustainable Food Systems, 2023)
In this paper, Pseudomonas syringae pv. actinidiae (Psa) was used to infect Cuiyu kiwifruits, and sterilization of exogenous vanillin on Psa and effects on the quality of the treated kiwifruits were investigated. According to the results of the sterilization study, the effectiveness of sterilization on the surface of kiwifruit was as follows: 61.29%, 92.33%, 96.79%, and 100% for the concentrations of vanillin at 5.0 mg•mL-1, 6.0 mg•mL-1, 7.0 mg•mL-1, 8.0 mg•mL-1, 9.0 mg•mL-1, and 10.0 mg•mL-1, respectively.According to the quality results, kiwifruits treated with 8.0 mg•mL-1vanillin exhibited a significant reduction in weight loss and rotting rate, with a decrease of 23.09% and 28.39% respectively, as compared to the control group. Additionally, thesetreated samples maintained a high level of total soluble solids, exhibited delayed degradation of total sugar content during a later period, inhibited an increase in respiratory intensity, and demonstrated increased firmness. Furthermore, vanillin treatment significantly increased the active values of superoxide, catalase, and peroxidase dismutase by 16.37%, 28.75%, and 23.92% respectively, compared to the control group. However, the levels of vitamin C and titratable acidity were not significantly affected by vanillin treatment.In conclusion, exogenous vanillin treatment exhibited potent sterilization capabilities against Psa, and effectively maintained the quality of kiwifruits during shelf life. This study could provide reference basis for controlling the propagation of Psa and developing a new and natural kiwifruit preservative.